244 ORAL ANTICOAGULANT PRESCRIBING IN OLDER PERSONS: AN AUDIT OF A COMMUNITY HOSPITAL REHABILITATION UNIT. (18th November 2021) - Ahern, E; Condon, J; Okpaje, B; Mohamed, A; Saleh, A; Ali, B; Mannion, M; Walsh, A; Gabr, A; Shanahan, E; Peters, C; O'Connor, M
Abstract: Background: Prescribing in older persons is complex and involves greater risk of drug-related harm. Prescribing appropriate anticoagulation balancing thromboembolic versus bleeding risk is essential with consideration to multiple comorbidities and polypharmacy. 27% of adults were prescribed inappropriate anticoagulation dosing in the GARFIELD-AF study. The Health Service Executive provides guidelines under the medicines management programme on prescribing anticoagulation treatment. The European Heart Rhythm Association (EHRA) published an updated practical guide on the use of non-vitamin K antagonist oral anticoagulants in patients with atrial fibrillation in 2021. Methods: A point prevalence audit was carried out in a community hospital rehabilitation unit, including all inpatients receiving oral anticoagulants (OAC). The data collected included: age, OAC prescribed, dose, documentation of indication, length of treatment, if a reduced dose was prescribed and reason why, creatinine clearance and reason for co-prescribing of an antiplatelet agent. Results were collected, analysed, and compared with the above guidelines. Results: 25 inpatients were included. 9 were on an OAC (36%). All patients were 70 years or over. DOACs were prescribed in 7 patients and warfarin in 2. All patients had a prescribing indication documented. All patients had an appropriate treatment duration documented. 3 OAC users were on a reduced dose, all of whom had an indication for a reduced dose documented. 1 patient was on medications with a documented drug–drug interaction. Only 3 patients had their creatinine clearance documented. No inpatients were co-prescribed an antiplatelet agent. Conclusion: Creatinine clearance is an important factor in prescribing of OAC and must be documented. Interventions to improve documentation of creatinine clearance will be explored and implemented. Consideration to drug–drug interactions in older patients with polypharmacy requires a multidisciplinary approach including pharmacy input.